Reflections on Reconfiguring Methods During COVID-19: Lessons in Trust, Partnership, and Care - McKinnon, Katharine; Hill, Ann; Appel, Margie; Hill, Deborah; Caffery, Jo; Pamphilon, Barbara (Frontiers in Sustainable Food Systems, 2022)
This paper is a set of reflections from researchers in the Center for Sustainable Communities, University of Canberra, drawing out emerging lessons from the process of re-configuring research methods during COVID-19. The pandemic has presented new spaces of negotiation, struggle, and interdependence within research projects and research teams. It has left researchers often uncertain about how to do their work effectively. At the same time, it has opened up opportunities to re-think how researchers undertake the work of research. In this paper we reflect on several current research programs that have had to undergo rapid design shifts to adjust to new conditions under COVID-19. The rapid shift has afforded some surprisingly positive outcomes and raised important questions for the future. In our reflections we look at the impact of COVID-19 at different stages of designing research with partners, establishing new relationships with partners and distant field sites, and data collection and analysis. We draw on Participatory Action Research (PAR) methodological ideas and highlight ways in which we have adapted and experimented with PAR methods during the pandemic. We reflect on the aspects of PAR that have assisted us to continue in our work, in particular, how PAR foregrounds diverse ways of knowing, being and doing, and prioritizes local aspirations, concerns and world views to drive the research agenda and the processes of social or economic change that accompany it. PAR also helps us to reflect on methods for building relationships of mutual trust, having genuine and authentic collaborations, and open conversations. We reflect on the potential lessons for PAR and community engaged research more generally. Amidst the challenges, our experience reveals new pathways for research practice to rebalance power relationships and support local place-conscious capacity for action.